The Alpha Male and Other Steamy Erotic Short Stories - Södergran, Alexandra (Saga Egmont, 2023)
\'The Alpha Male and Other Steamy Erotic Short Stories\' is a collection from LUST featuring stories from authors including Vanessa Salt, Alexandra Södergran, Sofia Fritzson, and Malva B. From alpha men and doctors to dangerous bad boys and fantasies with powerful prime ministers, there\'s something for every reader.